2002
DOI: 10.1038/sj.pcan.4500550
|View full text |Cite
|
Sign up to set email alerts
|

No association of the 5′ promoter region polymorphism of CYP17 gene with prostate cancer risk

Abstract: 4Hemocentro de São José do Rio Preto, Sáo Paulo, Brazil CYP17 gene encodes the enzyme cytochrome p450c17a, which mediates two steps in the steroid biosynthesis pathway. Steroid hormones are believed to play a key role in the etiology of prostate cancer. A polymorphic T?C transition in the 5 0 promoter region of CYP17 creates an additional Sp1-type (CCACC box) promoter site (allele A2). We have evaluated the genotypic and allelic distribution of this polymorphism among 92 prostate cancer patients in order to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Characteristics of studies eligible for the current meta‐analysis are presented in Table I 2, 10–28, 30–46. There are 357 papers relevant to the searching words.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of studies eligible for the current meta‐analysis are presented in Table I 2, 10–28, 30–46. There are 357 papers relevant to the searching words.…”
Section: Resultsmentioning
confidence: 99%
“…Three hundred two of 357 papers were excluded (126 duplicated of title; 40 were not in human; 36 were not case–control studies; 33 did not explore PCa; 31 did not explore CYP17 gene polymorphisms; 3 were meta‐analysis; 33 were reviews), leaving 55 studies for full publication review. Of these, 16 studies were excluded (7 studies did not explore cancer risk; 9 studies targeted on familial PCa risk), leaving 39 studies 2, 10–28, 30–47. Four articles examined the association in independent populations and thus each of them was treated as two separate studies 11, 36, 37, 46.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the subgroup analysis of the various genotype models, ethnicity was a major risk factor for prostate cancer. Several authors have reported the association between CYP17 rs743572 polymorphism and the risk of prostate cancer using African ancestry as a determinant ( Lunn et al, 1999 ; Kittles et al, 2001 ; Stanford et al, 2002 ; Cicek et al, 2004 ; Sarma et al, 2008 ; Beuten et al, 2009 ; Dos Santos et al, 2002 ). This meta-analysis disagrees with a study by Wang et al (2011) , who reported no significant association between CYP17 rs743572 polymorphism and prostate cancer in Caucasians and Asians.…”
Section: Discussionmentioning
confidence: 99%
“…Some case-control studies have reported an elevated risk for PCa being related to the A1/A2 or A2/A2 genotype (Lunn et al 1999;Gsur et al 2000;Haiman et al 2001;Kittles et al 2001;Yamada et al 2001;Sobti et al 2008;Souiden et al 2011), whereas other studies indicate an association between PCa and the A1/A1 genotype (Wadelius et al 1999;Habuchi et al 2000). Further studies have reported no difference in the distribution of the various alleles among healthy controls and PCa patients (Chang et al 2001;Latil et al 2001;Standford et al 2002;dos Santos et al 2002;Madigan et al 2003;Hamada et al 2007;Sivonova et al 2012;Cai et al 2012;KarimpurZahmatkesh et al 2013;Ersekerci et al 2015;Han et al 2015;Henríquez-Hernández et al 2015).…”
Section: Cyp17a1 Rs743572 Gene Polymorphismmentioning
confidence: 99%